Hubungan Personal Hygiene dengan Gejala Dermatitis pada Narapidana di Rutan Polres Bungo - Kantona, Rendi; Erfiana, Erma; Suriani, Rida (Fakultas Ilmu Kesehatan Universitas Dharmas Indonesia, 2025)
Risk factors for skin diseases include clean and healthy living behavior (PHBS), environmental sanitation conditions, availability of clean water, cleanliness of the body, nails, skin, clothing, and bed conditions. Transmission of skin diseases can occur through environmental components that contain disease agents and constantly interact with humans, namely water, air, food, and disease-transmitting insects and humans themselves. Residential density can also affect the process of disease transmission from one person to another (Achmadi, 2011). The purpose of this study was to determine the relationship between personal hygiene and dermatitis symptoms in prisoners at the Bungo Police Detention Center in 2024. The design of this study was an analytical survey with a cross-sectional approach. The number of samples in this study was 75 respondents. The results of the study on personal hygiene showed that 73.3% of prisoners with good personal hygiene did not experience symptoms of dermatitis. Based on the chi square statistical test, the p value was obtained = 0.000 <0.05, so it can be concluded that there is a relationship between personal hygiene and symptoms of dermatitis in prisoners at the Bungo Police detention center in 2024. It is hoped that prisoners at the Bungo Police detention center can maintain cleanliness in the detention center and personal hygiene.